A Multidisciplinary Study of a Group of Post‐Classical Cameos from the National Museum in Krakow, Poland. (30th April 2015) - Gołyźniak, P.; Natkaniec‐Nowak, L.; Dumańska‐Słowik, M.; Naglik, B.
Abstract : A group of 18 cameos dated from the 16th to 19th centuries (bearing motifs of Roman emperors and female members of their families) from the Constantine Schmidt‐Ciążyński collection was investigated with gemmological analyses, supported by non‐destructive mineralogical methods such as X‐ray diffraction (XRD) and micro‐Raman spectroscopy (RS) to ascertain the material used. Although there is no scientific method to date the specimens precisely, the mineralogical data supported by archaeological analyses enabled the estimation of the possible timing of the manufacture of the gems. As a result, the cameos were divided into four basic chronological groups: (1) Renaissance, (2) Baroque, (3) uncertain and (4) Classical and Neoclassical.